Effectiveness of the FIFA 11+ injury prevention programs in reducing acute lower back injury among soccer players: A systematic review and meta-analysis - Al Attar, W. S. A.; Bizzini, M.; Dvo*ák, J.; Pappas, E.; Alzahrani, H.; Al Shaman, M.; Elkins, M. R. (International Journal of Sports Science & Coaching, 2025)
Acute lower back injuries represent a significant concern in soccer players, often resulting in substantial morbidity and prolonged recovery periods. Despite various injury prevention programs, effective mitigation of acute lower back injuries remains challenging. The FIFA 11+ Injury Prevention Program is widely recognized for reducing general musculoskeletal injuries, yet its specific efficacy in lowering acute lower back injuries among soccer players has not been thoroughly evaluated. This systematic review and meta-analysis determined the effectiveness of the FIFA 11 + program in reducing acute lower back injuries among soccer players. A comprehensive literature search was conducted in PubMed, Cochrane Library, Web of Science, and PEDro from January 2010 to June 2025. Randomized controlled trials implementing the FIFA 11 + program and reporting acute lower back injury outcomes were selected. Search terms included `neuromuscular training,` `injury prevention programs,` `FIFA 11+,` `soccer,` and `back injury.` Our meta-analysis of five studies with 566,781 exposure hours and 61 total acute lower back injuries revealed significant reduction in injury incidence with the FIFA 11 + program (IRR = 0.37, 95% CI: 0.21-0.66; p < 0.001), representing a 63% reduction in injury risk. The absolute incidence changed from 1.09 to 0.39 injuries per 1000 h, with an absolute risk difference of 0.70 injuries/1000 h and a number needed to treat (NNT) of 1429 h. The I 2 = 0% indicated high consistency across studies. This review provides evidence supporting the FIFA 11 + program's efficacy in significantly reducing acute lower back injuries among soccer players. These findings underscore the program's value as a critical component of injury prevention strategies in soccer.